INCLUSIVE EDUCATION SYSTEM PROGRESS OF THE PROCESS - Oppoqxo‘jayev Xojixuja Azimjon o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article provides for the implementation of tasks aimed at improving the standard and quality of life of persons with disabilities, providing them with medical and social assistance and rehabilitation, improving education, expanding inclusive education, creating an information environment, international legal framework for the introduction of inclusive approaches to the educational process, international legal documents, as well as the laws of modern Uzbekistan, confirms the right to education regardless of socio-economic status and the right to receive information that does not discriminate against it on any basis.